2011
DOI: 10.1177/1933719110381140
|View full text |Cite
|
Sign up to set email alerts
|

Steroids That Induce Lung Maturation Acutely Affect Higher Cortical Function: A Fetal Magnetoencephalography Study

Abstract: Administration of betamethasone to expectant mothers was associated with acute change in higher cortical functions in the exposed fetuses. Implications regarding functional brain development need further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
1
8
2
Order By: Relevance
“…These results are in contrast to the acute delay of cortical AEP in human foetuses at 0.8 of gestational age (Schneider et al 2011). These results are in contrast to the acute delay of cortical AEP in human foetuses at 0.8 of gestational age (Schneider et al 2011).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…These results are in contrast to the acute delay of cortical AEP in human foetuses at 0.8 of gestational age (Schneider et al 2011). These results are in contrast to the acute delay of cortical AEP in human foetuses at 0.8 of gestational age (Schneider et al 2011).…”
Section: Discussioncontrasting
confidence: 78%
“…Reports in the literature only describe acute effects of glucocorticoids on brain function, such as delayed auditory-evoked potentials (AEP) in human foetuses within 3 h after glucocorticoid administration (Schneider et al 2011) and suppression of electrocorticogram (ECoG) activity in foetal sheep (Derks et al 1997, Schwab et al 2001b, Davidson et al 2011. Reports in the literature only describe acute effects of glucocorticoids on brain function, such as delayed auditory-evoked potentials (AEP) in human foetuses within 3 h after glucocorticoid administration (Schneider et al 2011) and suppression of electrocorticogram (ECoG) activity in foetal sheep (Derks et al 1997, Schwab et al 2001b, Davidson et al 2011.…”
mentioning
confidence: 99%
“…A single course of betamethasone decreased expression of neuronal cytoskeletal proteins and of the presynaptic marker synaptophysin, proteins that are necessary for brain development and neuronal functioning (94). The few human studies of brain development have evaluated the fetus or neonate and have shown that fetal exposure to glucocorticoid administration is associated with reduced neonatal cerebral cortical gray matter volume among preterm infants (36), decreased complexity of cortical folding and brain surface area among late preterm infants (37) as well as acute changes in fetal cortical functioning between 29 and 34 gestational weeks (95). …”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have shown harmful effects of fetal ACS exposure on auditory function [11, 20]. Church et al [11] demonstrated that repeated ACS treatment in rats resulted in a significantly prolonged neuronal transmission time along the auditory nerve and significantly elevated auditory brainstem response thresholds.…”
Section: Discussionmentioning
confidence: 99%